The resisters : a novel - Jen, Gish (Alfred A. Knopf, 2020)
An audacious wonder of a novel about baseball and a future America, from the always inventive and exciting author of The Love Wife and Who's Irish. The time: Some thirty-five years hence. The place: AutoAmerica--governed by "Aunt Nettie," an iBurrito of AI algorithms and the internet, in a land half under water. The people: Divided into the angelfair "Netted," whose fate it is to have jobs and live on high ground, and the mostly coppertoned "Surplus," whose jobs have been stripped and whose sole duty now is to consume, living in plastic houses that talk and multi-colored houseboats at the water's edge. Neither group is happy. The story: A Surplus family--he was once a professor, she is still a lawyer--has a girl child, Gwen, who's born with a golden arm. By two she can throw her toy animals straight to the same spot every time. When AutoAmerica and ChinRussia decide to revive the Olympics, suddenly Gwen, who's been playing in the Resisters League her parents have organized, is in great demand. Soon she's at angelfair university, Net U, falling in love with her baseball coach and facing questions of "crossing over," while her mother and her "group" are bringing charges before the botjudge about Surplus rights. An amazing story of a world that looks only too possible, and a family struggling to maintain its humanity in circumstances that daily threaten their every value as well as their very existence.